Pelatihan Penggunaan Aplikasi Rumah Belajar Bagi Siswa Yang Ada di Desa Ubung Sebagai Sarana Belajar Mandiri di Rumah - Baiq Rina Amalia Safitri; Wirawan Putrayadi; M. Fuaddunazmi; Pahriah Pahriah; Suryati Suryati (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
The purpose of this service is to minimize the negative impact of the internet. Methods of implementing community service, including: Preparation of activities; The mechanism for implementing the activity, before going into the field, it is necessary to do a number of things as a form of preparation, including: (a) Collect data and verify students in Ubung village. (b) Socialization of the program to students in Ubung village regarding the service program plan and the characteristics of local students who will be involved in implementing the work program. The results to be achieved from this Community Service activity or program are as much as possible for the benefit of local students, namely having a learning homeapplication and creating independent learning for students by utilizing the learning home application to reduce the negative impact of the internet and increase motivation and increase student learning achievement. In conclusion, by utilizing the learninghouse application, it is hoped that it can provide technology and skills to students on how to use the learning house application, so that it can reduce the negative impact of the internet.